2020
DOI: 10.22271/phyto.2020.v9.i1ai.10772
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and character association analysis for yield and attributing traits in tomato (Solanum lycopersicum L.) genotypes for protected cultivation

Abstract: The present study was carried out with fourteen genotypes of tomato at Polyhouse Complex, Department of Horticulture (Veg. & Flori.), BAU, Sabour during 2018-2019 to assess the genetic variability and character association for yield and attributing traits in tomato (Solanum lycopersicum L.) genotypes for protected conditions. The experiment was laid out in randomized block design with three replications. Data were recorded for sixteen morphological traits and five biochemical traits. The experimental results r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 6 publications
5
10
0
Order By: Relevance
“…High heritability combined with high genetic advance as percent of mean reflects characters governed by additive genes thus, direct selection for those characters could be rewarding (Poudel et al, 2021). In the present investigation all the traits have shown high heritability (broad sense) i.e., >60% similar to the findings of Hazra et al, (2019). In both sowing conditions high heritability coupled with high genetic advance as % of mean was found in thousand grain weight and Yield/plant.…”
Section: Resultssupporting
confidence: 68%
“…High heritability combined with high genetic advance as percent of mean reflects characters governed by additive genes thus, direct selection for those characters could be rewarding (Poudel et al, 2021). In the present investigation all the traits have shown high heritability (broad sense) i.e., >60% similar to the findings of Hazra et al, (2019). In both sowing conditions high heritability coupled with high genetic advance as % of mean was found in thousand grain weight and Yield/plant.…”
Section: Resultssupporting
confidence: 68%
“…The second Principal component (PC2) with Eigen value 3.234 accounted for 19.023 % of the total variation and loaded with the traits viz. days to physiological maturity (0.250), days to 50% flowering (0.225), growing degree days (0.363), panicle length (0.152), panicles per plant (0.148), photo thermal index (0.144), plant height (0.116) contributed in positive direction while spikelet fertility (-0.476), grain yield per plant (-0.395), critical temperature for reproductive stage (-0.348), helio-thermal unit (-0.330), photo-thermal unit (-0.165), hear use efficiency (-0.124) contributed negatively to the total Comparable studies and results in rice were obtained by the researchers like Das et al, 2014 andJakhar et al (2018). Table 3 showed that thirty-two genotypes of rice were grouped into six clusters using K-means nonhierarchical clustering.…”
Section: Resultsmentioning
confidence: 82%
“…Protected Cultivation works with the early foundation of seedlings and nursery plants. This enables farmers to get a head start on the growing season and speeds up crop development [46].…”
Section: ❖ Helps In Early Raising Of Nurserymentioning
confidence: 99%